2013
DOI: 10.12816/0002354
|View full text |Cite
|
Sign up to set email alerts
|

Impact of performance appraisal on employee’s performance involving the Moderating Role of Motivation

Abstract: Employee's performance is the major issue in an organization. Our study focuses on to find out the impact of performance appraisal on employee's performance and also analyses that motivation affects the relationship of performance appraisal and employee's performance. Twohypotheses are analyzed by using sampling techniques; we were select 150 numbers of employees as sample by using simple random sampling among the banks of Dera Ghazi Khan.Primary data were collect through standard questionnaire. For analyzing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
24
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(37 citation statements)
references
References 10 publications
2
24
0
2
Order By: Relevance
“…In accordance, performance appraisal (PA) is a regular and systematic process to evaluate employees' performance. It can be considered a reliable tool to make sure that the appropriate employees are filling the right positions within the organization (Iqbal et. al., 2014).…”
Section: Performance Management and Performance Appraisalmentioning
confidence: 99%
See 3 more Smart Citations
“…In accordance, performance appraisal (PA) is a regular and systematic process to evaluate employees' performance. It can be considered a reliable tool to make sure that the appropriate employees are filling the right positions within the organization (Iqbal et. al., 2014).…”
Section: Performance Management and Performance Appraisalmentioning
confidence: 99%
“…RAO ( 2015) also indicated that PA is essential to determine the success and failure of any PAC PAP PAE PAL MO JP organization implementation of the strategy and the growth through tracking the performance of the employee and the reasons that might motivate them. It was Iqbal et al ( 2014) who suggested relation between PA and employee's performance focusing on role of motivation. Aydın & Tiryaki (2018) later developed and examined a model on relationships between Motivation, Performance appraisal, and job performance in Turkey.…”
Section: Conceptual Framework and Research Hypothesesmentioning
confidence: 99%
See 2 more Smart Citations
“…It is the perception of a people who describe the intensity of behavior (Petri, 2004). Performance evaluation helps employees achieve goals, goals and guidance (Iqbal, Ahmad, Haider, & Batool, 2013).…”
Section: Performance Appraisalmentioning
confidence: 99%